Utility of FET-PET in detecting high-grade gliomas presenting with equivocal MR imaging features - Ameya D. Puranik; Mathew Boon; Nilendu Purandare; Venkatesh Rangarajan; Tejpal Gupta; Aliasgar Moiyadi; Prakash Shetty; Epari Sridhar; Archi Agrawal; Indraja Dev; Sneha Shah (World Journal of Nuclear Medicine)
High-grade gliomas, metastases, and primary central nervous system lymphoma (PCNSL) are common high-grade brain lesions, which may have overlapping features on magnetic resonance (MR) imaging. Our objective was to assess the utility of 18-fluoride-fluoro-ethyl-tyrosine positron emission tomography (FET-PET) in reliably differentiating between these lesions, by studying their metabolic characteristics. Patients with high-grade brain lesions suspicious for glioma, with overlapping features for metastases and PCNSL were referred for FET-PET by Neuroradiologists from Multidisciplinary Neuro-Oncology Joint Clinic. Tumor-to-contralateral white mater ratio (T/Wm) at 5 and 20 min was derived and compared to histopathology. Receiver operating characteristic curve analysis was used to find the optimal T/Wm cutoff to differentiate between the tumor types. T/Wm was higher for glial tumors compared to nonglial tumors (metastases, PCNSL, tuberculoma, and anaplastic meningioma). A cutoff of 1.9 was derived to reliably diagnose a tumor of glial origin with a sensitivity and specificity of 93.8% and 91%, respectively. FET-PET can be used to diagnose glial tumors presenting as high-grade brain lesions when MR findings show overlapping features for other common high-grade lesions.